Kajian Awal Prospek Bahan Galian Monasit Mengandung U dan Elemen Asosiasinya di Semelangan Ketapang, Kalimantan Barat - Subiantoro, Lilik; Soetopo, Bambang; Haryanto, Dwi (BRIN Publishing, 2011)
Semelangan study area included in the regional geology Ketapang. Geochemical analysis of sediment samples that represented showed that the region Semelangan Ketapang, District Nanga Tayap, Ketapang identified monazite deposite containing radioactive mineral. The monazite minerals containing rare earth element are potential. The presence of radioactive elements have been identified by the analysis granulometry of some pan consentrate samples. They containt of monazite grain mineral to reach 63% and some sample content of zircon grain mineral up to 40% (from total grains), grain analysis of rock samples are samples containing monazite 0.11 %. Activities study in this area is done by studying ecxisting data and laboratory data evaluation, which covering studies geological aspects, source rock, trap and plaser monazite deposits containing U, Th and REE and zircon. The objective is to obtain information about the character of geological and mineral resource distribution of monazite containing Th and U and rare earth elements in monazite and zircon. Source rock of the monazite minerals is a granite with aged 77-15 million (Yura - Late Cretaceous), including the S type granite group that formed in the alkali granite pegmatitic stage, which highly differentiated advanced at a temperature 550-6000°C. The radioactivity anomalous values is 400 c/s – 9200 c/s (biotite granite) with a mineral character of the form K-feldspar, quartz and plagioclase (K-feldspar to plagioclase ratio varies from 80-100 versus 10), containing minerals association such as thorit, monazite, zircon and alanit. The U content in granite rock ranging from 2.5 ppm - 64.8 ppm U. Lateral distribution plaser alluvial sediments contain monazite occupy flood plains of the valley between the hills, is located separately from the coastal plain and following the granite distribution pattern (source monazite). Monazite prospect region lies at the flood plains of the valley catcment area S. Pawan, S. Tulah and S Laur with a total area of 2.1135 million hectares.